Data Mining Rekomendasi Pemakaian Skincare - Simanjuntak, Pastima; Pangaribuan, Hotma; Syastra, Muhammad Taufik (MEANS (Media Informasi Analisa dan Sistem), 2021)
Facial treatments or skincare treatments contained in beauty care are divided into two categories, namely home treatment (such as giving face soap, morning cream, night cream, etc.) and direct care (such as facials, chemical peels, and so on). Home treatment facials consist of a variety of care products. Each home treatment product has a specific function both for treating the face or fixing the skin on consumers' faces such as acne, black spots, blackheads, oily skin, and others. Therefore, in order to determine the right home treatment product for consumers, knowledge of the usefulness of a home treatment product is needed. One of the factors of trade problems that exist in Batam City, there are still many products that enter without knowing whether the product is safe or not to be used, especially for cosmetic or skincare products where many cosmetic products are not licensed by BPOM but can still be traded to the people of Batam City. Finding skincare cosmetics that are good for the community is very difficult, because too many skincare products are sold in the market that do not have a BPOM permit and it will be dangerous for people who use these products. It is also due to the absence of a recommendation from a doctor or a beautician, which causes the wrong or bad skincare selection and will have a bad impact on one's face. The purpose of this study was to make recommendations for the use of skincare products in Batam City. For this reason, through this research, the researcher intends to apply one of the data mining techniques with the naÃ¯ve Bayes algorithm with software implementation using the Tanagra 4.1 software, where the results of this study can be used to see consumer buying patterns that have been neglected to increase product sales, and also see the decisions made to help recommendations for skincare use in Batam City.